2017
DOI: 10.1177/0363546516682233
|View full text |Cite
|
Sign up to set email alerts
|

Is an Anterolateral Ligament Reconstruction Required in ACL-Reconstructed Knees With Associated Injury to the Anterolateral Structures? A Robotic Analysis of Rotational Knee Stability

Abstract: The small changes in rotational stability after ALL/ITB sectioning would not seem to warrant the routine addition of an ALL reconstruction in primary ACL injuries. Clinical exceptions may exist, as in grossly unstable grade 3 pivot-shift knees and revision knees. However, the concern exists of overconstraining normal tibial rotations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
101
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(114 citation statements)
references
References 53 publications
7
101
2
4
Order By: Relevance
“…degrees of knee flexion adequately controlled knee kinematics without the need for an additional ALL reconstruction during a simulated pivot shift [38]. However, a residual increase of 5-7 degrees of internal tibial rotation occurs with ALC injury at high flexion angles, which is not controlled by ACL reconstruction.…”
Section: Biomechanics Of Lateralmentioning
confidence: 93%
“…degrees of knee flexion adequately controlled knee kinematics without the need for an additional ALL reconstruction during a simulated pivot shift [38]. However, a residual increase of 5-7 degrees of internal tibial rotation occurs with ALC injury at high flexion angles, which is not controlled by ACL reconstruction.…”
Section: Biomechanics Of Lateralmentioning
confidence: 93%
“…Most injured athletes will undergo ACL reconstruction, but there is an important risk of re-rupture (Paterno et al, 2014;Salmon et al, 2005) and only 65% of patients are able to return to their pre-injury level of sport (Ardern et al, 2014). In order to decrease the risk of a re-rupture, lateral extra-articular reconstruction (LER) is being performed with increasing frequency (Cerciello et al, 2018;Slette et al, 2016), since such a reconstruction is believed to improve the control of knee stability with respect to internal rotation and anterior translation (Inderhaug et al, 2017a(Inderhaug et al, , 2017bKatakura et al, 2017;Noyes et al, 2017;Sonnery-Cottet et al, 2015;Sonnery-Cottet et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Despite ongoing controversy in the literature, multiple biomechanical studies have demonstrated that the ALL plays a role in anterolateral rotatory instability related to the pivot-shift phenomenon [24,26,32,33,37,40,44,45,47,49]. Segond fractures are sometimes seen in periarticular knee fractures.…”
Section: Introductionmentioning
confidence: 99%